Left ventricular rotational mechanics in infants with hypoxic ischemic encephalopathy and preterm infants at 36 weeks postmenstrual age: A comparison with healthy term controls. Issue 2 (9th December 2016) - Breatnach, Colm R.; Forman, Eva; Foran, Adrienne; Monteith, Cathy; McSweeney, Lisa; Malone, Fergal; McCallion, Naomi; Franklin, Orla; El‐Khuffash, Afif
Abstract : Background and Aims: There is a paucity of data on left ventricle (LV) rotational physiology in neonates. We aimed to assess rotational mechanics in infants with hypoxic ischemic encephalopathy (HIE) and premature infants (<32 weeks) at 36 weeks postmenstrual age (PMA) (preterm group) and compare them with healthy term controls (term controls). We also compared the parameters in preterm infants with and without chronic lung disease (CLD). Methods: Echocardiography was performed within 48 hours of birth or at 36 weeks PMA. LV basal and apical rotation, twist (and torsion=twist/LV length), twist rate (LVTR), and untwist rate (LVUTR) were measured. One‐way ANOVA was used to compare values. Results: There was no difference in gestation (40.0 [39.1–40.3] vs 39.9 [39.0–40.9], P >.05) or birthweight (3.7 [3.4–4.1] vs 3.5 [3.2–3.9], P >.05) between the HIE group (n=16) and term controls (n=30). The preterm group (n=35) had a gestation and weight of 36.0 [34.6–36.3] weeks and 2.3 [2.0–2.4] kg. The HIE group had lower twist, torsion, LVTR, and LVUTR than the other two groups. The preterm group had a more negative (clockwise) basal rotation while the term group had a more positive (counterclockwise) apical rotation. Preterm infants with CLD had higher apical rotation, twist, and torsion when compared to infants without CLD. Conclusion: Infants with HIE have reduced rotational mechanics. Preterm infants at 36 weeks PMA have comparable measurements of twist to term infants. This is achieved by predominant basal rather than apical rotation. Infants with CLD have increased apical rotation.